What the 2012 Census of Agriculture Is Telling Us about Miami-Dade County - Edward Evans; Fredy H. Ballen (EDIS)
Agriculture is an important contributor to Florida’s economy. Only the tourism industry employs more Floridians. In 2012, agricultural output was estimated at $141.8 billion, accounting for 14.9% of the state’s gross domestic product, and providing employment for 20.8% of the state’s labor force. Monitoring the performance of the sector over time is therefore of critical importance to various stakeholders. This 8-page publication focuses on the Agricultural Census data for Miami-Dade County and specifically examines trends over the 15-year period from 1997 to 2012 with the aim of highlighting some of the major trends occurring in the Miami-Dade County agricultural sector. In general, the data show that in spite of challenging times, the agricultural industry has remained important, contributing $604 million to the Florida economy in 2012. Written by Edward Evans and Fredy H. Ballen, and published by the Food and Resource Economics Department, October 2016.